National-Scale Geospatial Modelling of Pyrrhotite in Bedrock Across Canada: A Pilot Study - Honsberger, Ian W.; Ford, Angela; McDonald, Daniel (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2024)
The most abundant iron sulphide minerals in igneous, metamorphic, and some sedimentary rocks are FeS2 (pyrite/marcasite) and Fe1-xS (pyrrhotite). The oxidation of pyrite and pyrrhotite in bedrock aggregates and mine tailings is undesirable to infrastructure and the environment because such chemical reactions are linked with concrete deterioration and acid mine drainage, respectively. The oxidation rate of pyrrhotite is up to one hundred times greater than that of pyrite; thus, pyrrhotite oxidation is of particular concern to society. Pyrrhotite-bearing concrete aggregates may lead to rapid expansion cracking and failure of critical concrete infrastructure including bridges, buildings, and houses, posing a significant safety concern. Additionally, premature disintegration of concrete requires replacement of concrete, leading to excessive aggregate resource extraction and associated increases in CO2 emissions. Considering the widespread concrete infrastructure across Canada, the distribution of pyrrhotite in bedrock used for aggregate is of fundamental importance to the short- and long-term safety of Canadians at the national, regional, and local scales.This pilot study details the initial steps taken to generate national-scale geospatial models of pyrrhotite occurrences in bedrock across Canada and illustrates the associated map products. In total, 12,577 known pyrrhotite occurrences were identified from publicly available provincial and territorial mineral occurrence datasets. The overall modelling strategy involved normalizing the number of pyrrhotite occurrences with respect to the total surface area of major bedrock types and characterizing three different classes of pyrrhotite occurrence density (< 1, 1–4, and 4–10 occurrences/1000 km2). The maps illustrate that pyrrhotite occurrence density is highest in volcanic rocks and undifferentiated sedimentary and volcanic rocks, moderate in intrusive and unknown rocks, and lowest in sedimentary and metamorphic rocks. Sedimentary rocks with no pyrrhotite occurrences span large surface areas across central-western Canada thus resulting in an overall low pyrrhotite occurrence density (< 1 occurrence/1000 km2) for this rock type, despite the fact that numerous pyrrhotite occurrences are identified in sedimentary rocks and may be abundant locally or regionally. Volcanic, undifferentiated sedimentary and volcanic, intrusive, and unknown rocks occur throughout the Canadian Shield of central and northern Canada, the Cordillera of western Canada, and the Appalachians of eastern Canada, but bedrock type and associated occurrence density are highly variable within these geological domains.Comparison of pyrrhotite occurrence density maps for Canada with pyrrhotite permissive geology maps for the United States of America illustrates that rocks with a high pyrrhotite occurrence density in Canada (volcanic rocks and undifferentiated sedimentary and volcanic rocks), are contiguous overall with areas of pyrrhotite potential in the United States. Inconsistencies across the international border reflect the differing methodologies and assumptions consisting of a statistically based approach for Canada and a qualitative approach for the United States. In the Cordillera and Appalachians, such discontinuities across the international border may reflect the underestimation of pyrrhotite occurrences in sedimentary rocks of Canada because of the impact of high surface area on the pyrrhotite occurrence density calculations.The maps presented herein are a first step in illustrating the distribution of pyrrhotite-bearing bedrock across Canada and greater North America. These national-scale map products are useful first-order references for selecting regions for follow-up studies on bedrock pyrrhotite occurrences. Regional and local geospatial analysis combined with field work for ground truthing will be important aspects of future research, especially in the vicinity of population centres where bedrock is utilized for concrete aggregate. Detailed regional and local studies of pyrrhotite occurrences in bedrock will help guide the extraction of safe concrete aggregate and contribute to the long-term sustainability of bedrock resources, safe infrastructure, and a habitable climate.